Wealth selection in a financial market with heterogeneous agents - Mikhail Anufriev; Pietro Dindo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
We study the co-evolution of asset prices and individual wealth in a financial market populated by an arbitrary number of heterogeneous, boundedly rational agents. Using wealth dynamics as a selection device we are able to characterize the long run market outcomes, i.e. asset returns and wealth distributions, for a general class of investment behaviors. Our investigation illustrates that market interaction and wealth dynamics pose certain limits on the outcome of agents' interactions even within the wilderness of bounded rationality. As an application we consider the case of heterogeneous mean-variance optimizers and provide insights into the results of the simulation model introduced by Levy, Levy and Solomon (1994).
Keywords: G12; D84; C62; 330; Heterogeneous agents; Asset pricing model; Bounded rationality; CRRA framework; Levy-Levy-Solomon model; Evolutionary Finance